France : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
The paper identifies France's structural reforms that would yield the largest competitiveness gains based on macro-empirical evidence, and reviews signs of potential gains from a deregulation of the services sector. It is expected that completing deregulation in the services sector would benefit the entire French economy, by boosting productivity and exports. Econometric results have estimated the impact of reducing the labor taxation and labor market rigidities and of increasing innovation to the average level of other advanced countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet